Strengthening Digital-Based Public Service Innovation as a Strategy to Enhance the Organizational Performance of the Makassar City Government - Muhammad Luthfi Siraj; Suprianto; Didik Iskandar; Andi Onasis; Muhammad Iqbal (CV. Era Digital Nusantara, 2026)
Digital transformation has become a crucial strategy for enhancing the quality of public services and the performance of local government organizations. However, the implementation of digital-based public service innovations still faces challenges regarding system integration, the digital capacity of civil servants, business process transformation, and the measurement of innovation's impact on public value creation. This study aims to analyze the strengthening of digital-based public service innovation as a strategy to improve the organizational performance of the Makassar City Government, focusing on the digital transformation process, organizational capabilities, and public value creation. A qualitative approach with a case study design was employed. Data were gathered through in-depth interviews with informants involved in Electronic-Based Government System (SPBE) management and digital public service delivery, alongside an analysis of policy documents and government reports. Data analysis utilized the interactive model developed by Miles, Huberman, and Saldaña, comprising the stages of data condensation, data display, and conclusion drawing. The study yielded three key findings. First, public service digitalization in Makassar City has progressed through the implementation of SPBE, Smart City initiatives, and various digital platforms, yet it still requires stronger system integration and the transformation of organizational business processes. Second, the digital capabilities of civil servants (ASN) serve as a strategic factor in the success of innovation, as they determine the organization's ability to manage change and leverage technology optimally. Third, public service innovation needs to shift from a mere digital service delivery approach toward public value creation to sustainably enhance service quality, public trust, and organizational performance.